News from Baltic amber: a new tribe of extinct Paleogene ironclad beetles (Coleoptera: Zopheridae: Zopherinae) - Alekseev, Vitalii I.; Nabozhenko, Maxim V. (Zootaxa, 2023)
A new extinct monotypic genus of the ironclad beetles, Zopheromimus auriborussiensis gen. et sp. nov., is described and illustrated based on an inclusion in Baltic amber. The new Eocene fossil taxon is placed in Zopheromimini trib. nov., a new tribe within the subfamily Zopherinae, and compared with related extant beetles of the subfamily. The genus Yantaroxenos Nabozhenko, Kirejtshuk et Merkl, 2016 is transferred from the tribe Belopini (Tenebrionidae: Lagriinae) to the newly described tribe of Zopheridae.